1997
DOI: 10.1001/archinte.1997.00440380069007
|View full text |Cite
|
Sign up to set email alerts
|

Adult Bacteremic Pneumococcal Pneumonia in a Community Teaching Hospital, 1992-1996n

Abstract: We found a recent increase in the prevalence of bacteremic pneumococcal pneumonia in adults. Gram stain of sputum is useful, but sputum culture is less sensitive in the diagnosis of pneumococcal pneumonia. The fatality rate remains high. More effort should be made at prevention using pneumococcal immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 0 publications
5
17
1
2
Order By: Relevance
“…These findings are consistent with one previously published study. 8 This detailed analysis of adult bacteraemic pneumococcal pneumonia in a community teaching hospital during the years 1992-1996 found that, among 108 patients, only 73.2% presented with a leukocyte count >11,000 cells/mm 3 . The authors noted that leukocytosis was associated with a better prognosis than a normal leukocyte count and leukopenia, 8,15 findings that were not confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with one previously published study. 8 This detailed analysis of adult bacteraemic pneumococcal pneumonia in a community teaching hospital during the years 1992-1996 found that, among 108 patients, only 73.2% presented with a leukocyte count >11,000 cells/mm 3 . The authors noted that leukocytosis was associated with a better prognosis than a normal leukocyte count and leukopenia, 8,15 findings that were not confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pneumococcal pneumonia the peripheral WBC count generally exceeds 11,000/mm 3 , 7,8 although it can be lower than 6,000/mm 3 in 5-10% of patients. Such a low count has been found to be strongly associated with a poor prognosis.…”
Section: T I O N P R O H I B I T E Dmentioning
confidence: 96%
See 2 more Smart Citations
“…Diabetes is one of the conditions associated with recurrent pneumonia [83]. Bacteraemic pneumococcal pneumonia occurs relatively commonly in diabetic individuals [84,85], but a recent population-based study found a death rate that was similar to that in non-diabetic patients with this condition [86]. However, the adverse impact of diabetes on morbidity and mortality during influenza epidemics has long been recognized [87].…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%